Trends in maternal mortality in Suriname: 3 confidential enquiries in 3 decadesAJOG Global reports at a Glance - Lachmi R. Kodan, MD, MSc, PhD; Kim J.C. Verschueren, MD, PhD; Raez Paidin, MD; Rubinah Paidin, MD; Joyce L. Browne, MD, MSc, PhD; Kitty W.M. Bloemenkamp, MD, PhD; Marcus J. Rijken, MD, PhD (Elsevier, 2021)
BACKGROUND: The Sustainable Development Goal target 3.1 aims to reduce the global maternal mortality ratio to less than 70 per 100,000 live births. Great disparities reported in maternal mortality ratio between and within countries make this target unachievable. To gain more insight into such disparities and to monitor and describe trends, confidential enquiries into maternal deaths are crucial. OBJECTIVE: We aimed to study the trend in maternal mortality ratio, causes, delay in access and quality of care, and "lessons learned" in Suriname, over almost 3 decades with 3 confidential enquiries into maternal deaths and provide recommendations to prevent maternal deaths. STUDY DESIGN: The third national confidential enquiry into maternal deaths was conducted between 2015 and 2019 in Suriname by prospective, population-based surveillance and multidisciplinary systematic maternal death review. Subsequently, a comparative analysis with previous confidential enquiry into maternal deaths was performed: confidential enquiry into maternal deaths I (a prospective study, 1991-1993) and confidential enquiry into maternal deaths II (a retrospective study, 2010-2014). RESULTS: We identified 62 maternal deaths and recorded 48,881 live births (maternal mortality ratio, 127/100,000 live births) between 2015-2019. Of the women who died, 14 of 62 (23%) were in poor condition when entering a health facility, whereas 11 of 62 (18%) died at home or during transportation. The maternal mortality ratio decreased over the years, (226 [n=64]; 130 [n=65]; and 127 [n=62]), with underreporting rates of 62%, 26%, and 24%, respectively in confidential enquiry into maternal deaths I, II and III. Of the women deceased, 36 (56%), 37 (57%), and 40 (63%) were of African descent; 46 (72%), 45 (69%), and 47 (76%) died after birth; and 47 (73%), 55 (84%), and 48 (77%) died in the hospital, respectively, in confidential enquiries into maternal deaths I, II, and III. Significantly more women were uninsured in confidential enquiry into maternal deaths III (15 of 59 [25%,]) than in confidential enquiry into maternal deaths II (0%) and I (6 of 64 [9%]). Obstetrical hemorrhage was less often the underlying cause of death over the years (19 of 64 [30%], vs 13 of 65 [20%], vs 7 of 62 [11%]), whereas all other obstetrical causes occurred more often in confidential enquiry into maternal deaths III (eg, suicide [0; 1 of 65 (2%); 5 of 62 (8%)]) and unspecified deaths (1 of 64 [2%]; 3 of 65 [5%]; and 11 of 62 [18%] in confidential enquiry into maternal deaths I, II and III respectively). Maternal deaths were preventable in nearly half of the cases in confidential enquiry into maternal deaths II (28 of 65) and III (29 of 62). Delay in quality of care occurred in at least two-thirds of cases (41 of 62 [65%], 47 of 59 [80%], and 47 of 61 [77%]) over the years. CONCLUSION: Suriname's maternal mortality rate has decreased throughout the past 3 decades, yet the trend is too slow to achieve the Sustainable Development Goal 3.1. Preventable maternal deaths can be reduced by ensuring high-quality facility-based obstetrical and postpartum care, universal access to care especially for vulnerable women (of African descent and low socioeconomic class), and by addressing specific underlying causes of maternal deaths.